Effect of White and Black Rice Addition on Robusta Coffee Powder and Brews Characteristics - Yustina, Ita; Abadi, Farid R. (El-Hayah : Jurnal Biologi, 2017)
The processing methods of coffee bean are various in different regions in Indonesia. One of the methods is by adding the material of coffee bean with other ingredients such as rice. This research was aimed to investigate the effect of adding white and black rice into the yield and quality of robusta coffee within its powder and brews. The experiment used the completely randomized design, with three treatments Â namely: pure coffee; coffee+white rice; and coffee+black rice. Observation parameters consisted of: rendement;color; organoleptical properties; and antioxidant activity. The results showed that the addition of black or white rice (30%) did not affected the yield, pannelist's preference for color, and the bitter level of coffee brews. However, the addition of white or black rice had a significant effect on the degree of lightness and the antioxidant activity of the coffee powder, also the panelist's preference for the aroma and taste for coffee brews. The black rice addition showed to be more preferred whichÂ  scored 3.18 for aroma and 3.55 for taste than white rice addition in coffee brews. Moreover, the color of the coffee powder of coffee + black rice became brighter (L = 35), and the antioxidant activity was increased to reach 44.74% as the highest among other treatments. The black rice addition could be used to improve the antioxidant activity of the commercial robusta coffee powder and brews with fairly consumer acceptance.Â